Facial emotion recognition in myotonic dystrophy type 1 correlates with CTG repeat expansion. Issue 2 (17th January 2006) - Winblad, S; Hellström, P; Lindberg, C; Hansen, S
Abstract : Objective: To investigate the ability of patients with myotonic dystrophy type 1 to recognise basic facial emotions. We also explored the relationship between facial emotion recognition, neuropsychological data, personality, and CTG repeat expansion data in the DM-1 group. Methods: In total, 50 patients with DM-1 (28 women and 22 men) participated, with 41 healthy controls. Recognition of facial emotional expressions was assessed using photographs of basic emotions. A set of tests measured cognition and personality dimensions, and CTG repeat size was quantified in blood lymphocytes. Results: Patients with DM-1 showed impaired recognition of facial emotions compared with controls. A significant negative correlation was found between total score of emotion recognition in a forced choice task and CTG repeat size. Furthermore, specific cognitive functions (vocabulary, visuospatial construction ability, and speed) and personality dimensions (reward dependence and cooperativeness) correlated with scores on the forced choice emotion recognition task. Conclusion: These findings revealed a CTG repeat dependent facial emotion recognition deficit in the DM-1 group, which was associated with specific neuropsychological functions. Furthermore, a correlation was found between facial emotional recognition ability and personality dimensions associated with sociability. This adds a new clinically relevant dimension in the cognitive deficits associated with DM-1.